COMPUTERIZED TOMOGRAPHIC SCANNING OF BRAIN FOR EVALUATION OF CHILDREN WITH DELAYED MILESTONES - Raza, Saleem; Malik, Bashir Ahmad; Siddiqi, Hammad Ahmad (Pakistan Armed Forces Medical Journal, 2011)
Objective: To assess the utility of Computerized Tomographic (CT) scanning of brain in the evaluation of children with delayed milestones. Study Design: Cross-sectional retrospective study. Place and Duration of Study: Department of Radiology, Pakistan Air Force Hospital, Islamabad from April 2007 to September 2009. Patients and Methods: We retrospectively reviewed the referral forms of CT scanning of brain for evaluation of children with delayed milestones. A total of 48 patients had a CT brain for evaluation of delayed milestones. They were divided into two groups. There were 15 patients in group A, who had significant history and clinical findings. Group B had 33 patients, in whom there was no clue to the etiology of developmental delay. The results of their CT scans of brain were compiled and analyzed. Results: Out of a total of 15 patients in group A, fourteen (93.3%) had an abnormality. Mild cerebral atrophy was seen in 11 patients, two had calcification in basal ganglia and one had leukodystrophy. No abnormality was seen in CT scan of brain in group B patients. Conclusion: CT scanning of brain is useful in reaching a diagnosis of delayed developmental milestones where there are significant historical and abnormal physical findings.